Characterization of Tibetan Medicine Zuota by Multiple Techniques. (5th September 2013) - Zhao, Xiao-Yan; Sun, Mei; Wang, Jing-Xia; Xu, Yun-Zhang; Liu, Yuan; Zhang, Zhi-Feng; Lu, Lu-Yang
Abstract : Zuota is regarded as the king of Tibetan medicine. However, due to the confidentiality of this precious medicine, the scientific characterization of Zuota is very scarce, which limits the pharmacology and biosafety studies of Zuota . Herein, we collected four different Zuota samples from Tibet, Qinghai, Gansu, and Sichuan and characterized them by multiple techniques. Our results showed that Zuota was mainly an inorganic mixture of HgS, sulfur, and graphite. Morphologically, Zuota samples were composed of nanoparticles, which further aggregated into microsized particles. Chemically, the majorities of Zuota were S and Hg (in the forms of HgS and pure sulfur). All samples contained pure sulfur with orthorhombic crystalline. Zuota from Qinghai province had different HgS crystalline, namely, hexagonal crystalline. The others were all face-centered cubic crystalline. Carbon in Zuota NPs was in the form of graphite. The implication to future studies of Zuota was discussed.